Effect of Post-grazing Sward Height on Ingestive Behavior, Dry Matter Intake, and Milk Production of Holstein Dairy Cows - Menegazzi, Gabriel; Giles, Pamela Yanina; Oborsky, Matías; Fast, Oliver; Mattiauda, Diego Antonio; Genro, Teresa Cristina Moraes; Chilibroste, Pablo (Frontiers in Animal Science, 2021)
Sward height is strongly related to the daily dry matter intake of grazing dairy cows, which consequently determines animal performance. Despite that, few studies have explored the potential to increase milk production by managing post-grazing sward height. An experiment was carried out to evaluate the effect of three defoliation intensities on a Lolium arundinaceum-based pasture on frequency and length of grazing meals and ruminating bouts, daily grazing and ruminating time, feeding stations and patches exploration, and dry matter intake and milk production of dairy cows. The treatments imposed were three different post-grazing sward heights: control (TC), medium (TM), and lax (TL), which were managed with 6, 9, and 12 cm of post-grazing sward heights during autumn and winter, and 9, 12, and 15 cm of post-grazing sward heights during spring, respectively. Thirty-six autumn-calving Holstein cows were grouped by parity (2.6 ± 0.8), body weight (618 ± 48) kg, and body condition score (2.8 ± 0.2) and randomized to the treatments. The pasture was accessed from 08:00 to 14:00 and 17:00 to 03:00 during spring and no supplement was involved during the evaluation period. Daily grazing time averaged 508 ± 15 min and was not affected by treatment. The reduction of post-grazing sward height increased the length of the first grazing session in the morning and the afternoon. The number of grazing sessions was greater on TL than on TM, with no difference in TC. The number of feeding stations (the hypothetical semi-circle in front of an animal from which the bites were taken without moving the front forefeet) visited was less on TC than on TL, and neither of them differed from TM. Dry matter (DM) intake was lesser on TC than on TM and TL (14.7 vs. 17.8 kg DM). Milk production during the evaluation period was 13.1, 16.2, and 18.7 kg/day for TC, TM, and TL, respectively. The milk fat, protein, and lactose content did not differ between treatments. The cows on TC exhibited a lower intake rate, although they were less selective, probably as a consequence of the sward structure of TC treatment. The cows on TM adopted a compensation mechanism which allowed them to achieve the same dry matter intake as cows on TL, but lower milk production. The cows on TL were more selective than TC and TM resulting in higher digestible dry matter intake and consequently higher milk production. The intensity of defoliation impacts on the animal-plant interaction, and constitutes a valuable management tool that can be used to boost forage intake and milk production. The new developments on information technology would allow researchers to link behavioral data with response variables (e.g., milk production, health, welfare, etc.) at different spatio-temporal scales and support short and long-term management decisions.